(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2022)
Background: Successive waves of COVID-19, the pandemic of 2020 is still sweeping throughout the world in terms of morbidity and mortality. The speed of development of the vaccines, preclinical trials, clinical trials, all are unprecedented. So there remained a concern about the short- and long-term health effects (Wanted and unwanted) of these vaccines. Bangladesh is fortunate enough to get supply of vaccine (Oxford-AstraZeneca) early in the course. As expected, the vaccination program was phased and the population was stratified according to health risk. Health care workers were among the first groups receiving that vaccine in Bangladesh. A study was conducted with the objectives of assessing and describing the adverse events following vaccination against SARSCoV-2 and also of establishment of a post vaccination support clinic in Chittagong Medical College Hospital (CMCH) Bangladesh from February 2021 to June 2021. Materials and methods: Prospective surveillance was done among the vaccine recipients healthcare workers of CMCH and their family members. Participants were enrolled after the start of first dose vaccination from February in CMCH and also after the second dose vaccination from April 2021. A number of 1334 participants were signed-up after first dose of vaccination and were followed up through second dose. The initiative was taken to address the complications arising from vaccination among the vaccine recipients both over telephone and also in ward 16 of CMCH for those whose complaints warranted a physical examination. Results: A total of 1334 Oxford-AstraZeneca COVID-19 vaccine (AZD1222) (Covishield) vaccinated health care workers and their family members participated in the study, with age range from 18 to 89 years. More than 78% of them were within their 2nd to 6th decade of age. 19.2% of respondents were above 60 years old. Males were predominant in numbers than females (61.3% Vs 38.7%). Among the respondents, the majority were physicians by profession (51.4%). Among the recipients, about 30% had previous comorbid diseases; hypertension and diabetes mellitus being more common (18.6% & 14.4%). An elaborate distribution of ‘Adverse Events Following Immunization’ (AEFI) was furnished. 37.3% participants were identified as suffering from symptoms after receiving the first dose of COVID–19 vaccinations, while only 11.4% were affected after taking the second dose. Common symptoms experienced by the respondents after first and second doses of the vaccination were as follows: mild fever (Temp< 38° C), muscle pain, pain at immunization site, tenderness and soreness at injection site, headache, tiredness, fatigue, chills, dizziness etc. Recipients aged more than 50 years suffered significantly more symptoms. Gender and comorbidities did not influence in developing symptoms. There was no serious or fatal event. Conclusion: According to the findings of this study the used vaccine Oxford-AstraZeneca AZ AZD1222 (Covishield) appear to be reasonably safe in adult population with few physical discomforts which are neither life threatening nor serious. JCMCTA 2022 ; 33 (1) : 4-8